UNVEILING THE SELF-PRESENTATION TACTICS ON FACEBOOK: THE ROLE OF PERSONALITY TRAITS - Martskvishvili, Khatuna; Mestvirishvili, Maia; Khechuashvili, Lili; Nemanishvili, Tekla (Georgian Psychological Journal, 2023)
Self-presentation tactics on Facebook are subjects of study by researchers in the area of Social Media Retrieval. Social networking sites, such as Facebook, offer social scientists a unique opportunity to observe behavior in a real setting and increase the accessibility of study participants from different countries and demographic groups. Modern social networking sites platforms provide abundant behavioral cues, including self-presentation tactics, which can potentially reveal an user’s personality. In the present study, we analyze two components of Facebook use: motives and self-presentation tactics, and explore the ways in which they associate with the Dark Triad and HEXACO personality traits. personality traits predict self-presentation tactics on Facebook; they lead individuals to certain motives for Facebook use and consequently, to specific self-presentation tactics. Besides, the motives of Facebook use mediate the relationship between personality traits and self-presentation tactics. The current study sheds light on the mechanisms of how personality traits might lead to self-presentation tactics on Facebook; it enhances existing knowledge about the relationship between motives of Facebook use and the self-presentation tactics employed by the Facebook users to achieve their goals.